EVALUATION OF UNSAFE ACTIONS, UNSAFE CONDITIONS, AND POSITIVE OBSERVATIONS AT A FUEL TERMINAL USING THE BEHAVIOR BASED SAFETY OBSERVATION APPROACH - Syifa Hamidya; Eky Susilowati; Nasya Adelia Putri; Nur Ulfah (Departemen K3 FKM Universitas Halu Oleo, 2025)
An oil fuel terminal serves as a storage facility for petroleum products, where work activities are inherently associated with a high level of occupational safety and health (OSH) risks. This study aims to evaluate unsafe Actions, unsafe conditions, and positive observations at the Oil Fuel Terminal using the Behavior-Based Safety Observation (BBSO) approach. This method enables proactive identification and prevention of potential hazards by engaging workers in reporting field findings. A descriptive quantitative design was employed, utilizing secondary data derived from BBSO reports in 2020. The study population comprised all workers observed through the BBSO system between January and December 2020. As the data were collected from actional observation reports over a one-year period, all recorded BBSO findings were included as the research sample. The sampling method applied was total sampling, as every finding was incorporated into the analysis. The results indicate that positive observations dominated the reports, accounting for 1,409 cases (68.86%), while unsafe conditions and unsafe Actions comprised 637 cases (31.14%). Within the category of unsafe conditions and Actions, the most prevalent subcategories were safety awareness and behavior with 132 cases (20.7%), followed by housekeeping with 106 cases (16.64%). The majority of unsafe condition and action findings were located at the security gate, totaling 215 cases (33.7%), suggesting that screening procedures were conducted effectively to prevent hazards from entering restricted zones prior to workers’ access